(untitled) (Research, Society and Development, 2021)
The present review study sought to compile information available in the literature regarding the studies of performance analysis in futsal with the purpose of tracing the reality that the scientific production is about the performance analysis in futsal. To this end, the search for academic publications was conducted in the EBSCO (SportDiscus), PubMed, Web of Science, SciElo, Scopus, BVS and EMBASE databases with the following descriptors: performance analysis, notational analysis, game analysis, tactical analysis, game pattern, futsal and indoor soccer, in English, Spanish and Portuguese. Fifty articles were selected according to the established inclusion and exclusion criteria. It returned 238 actions analyzed in players and games in futsal, and the most analyzed were the pass, kick and goal. They were distributed as follows, according to their attributes: technical (65.97%), tactical (19.75%), goalkeeper (8.40%) and set pieces (5.88%). Thus, the technical attributes are the ones of greatest interest among researchers in the area. We recommend more studies directed at women’s futsal, goalkeepers, and defensive actions (tackles, steal of the ball, and interceptions). The future of performance analysis in futsal is addressed.